2012
DOI: 10.1177/097135571102100102
|View full text |Cite
|
Sign up to set email alerts
|

Opportunity Recognition in Social Entrepreneurship

Abstract: Opportunity recognition (OR) is at the very heart of entrepreneurship. However, research on OR in the context of social entrepreneurship is still in its early stages. First, this article identifies, codifies and analyses OR-relevant articles on social entrepreneurship (SE) through the lens of Sarasvathy's three views of entrepreneurial opportunity recognition. In the second step, statistical methods are applied on the results to indicate possible correlations among different schools of thought in SE and views … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
62
2
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(70 citation statements)
references
References 72 publications
(79 reference statements)
4
62
2
2
Order By: Relevance
“…According to our results, during the crisis the influence of perceived opportunities on social entrepreneurship increased 37 % compared with the period before the crisis. Similar to previous results (Lehner & Kaniskas, 2012;Roy et al, 2014;Tominc & Rebernik, 2007), perceived opportunities are found to be related to entrepreneurial intentions and are a key driver in the decision to start a new business.…”
Section: Resultssupporting
confidence: 87%
“…According to our results, during the crisis the influence of perceived opportunities on social entrepreneurship increased 37 % compared with the period before the crisis. Similar to previous results (Lehner & Kaniskas, 2012;Roy et al, 2014;Tominc & Rebernik, 2007), perceived opportunities are found to be related to entrepreneurial intentions and are a key driver in the decision to start a new business.…”
Section: Resultssupporting
confidence: 87%
“…Although some concepts have been proposed in the literature, there is still no consensus among researchers, because the field is under development (Phillips, Lee, Ghobadian, O'Regan, & James, 2015). In relation to the empirical investigations in the context of SI, as Phillips et al (2015) state, there are three predominant fields: the role of social entrepreneur (Austin, Stevenson, & Wei-Skillern, 2006;Lehner & Kansikas, 2012;Ruvio & Shoham, 2011;Zahra, Gedajlovic, Neubaum and Shulman (2009), the partnership relationship (Edwards, Matti, & Alcántara, 2012;Lettice & Parekh, 2010) and the importance of the institutional environment (Desa, 2012;Moore, Westley, & Nicholls, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, disability alone sometimes suffices to be the main trigger for differently abled persons to face insurmountable obstacles that prevent them from accessing meaningful employment (Sayce, 2012;Ormerod & Newton, 2013). Nonetheless, differently abled persons have to recognise entrepreneurial opportunities to start a business venture (Lehner & Kansikas, 2012). Thus, starting a business venture sometimes is forced by circumstances such as loss of a job, being laid off and companies restructuring or relocating.…”
Section: Starting a Business Venture 53mentioning
confidence: 99%